Syndebukkemekanismen i nilotisk kongedømme - Simonse, Simon (Religionsvidenskabeligt Tidsskrift, 1992)
Den bristede og den opskærne mave. In a structural analysis of the ritual in the treatment of the stomach of the dead king (or queen) in some Upper-Nilotic societies, the role of the kind a a "rain maker" (or the opposite) is demonstrated. Furthermore, the king is the point around which social tensions and rivalry is concentrated, either to be solved by him or be acted out with the king as a scapegoat. Girard’s "scapegoat theory", while basically affirmed, is criticised on some important points: especially, the efficacy of the scapegoat mechanism does not seem to be dependent on the ignorance of the real psycho-sociological forces which are in play. To some informants, the treatment of the king assumes therefore the contours of an inescapable and therefore tragic necessity.